1970
DOI: 10.1111/j.1749-6632.1970.tb55940.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Myo-Inositol Metabolism in Galactosemia

Abstract: During the investigation of galactitol accumulation in the tissues of galactosemia patients, it was observed that the concentration of free and lipid-bound myo-inositol in the brain was lower than that in normal brain.l.2 At various stages of development, brains from rats fed a diet containing 35% galactose contained somewhat lower concentrations of inositol than did those from comparable control^.^ These findings suggested a possible relationship between galactosemia and myo-inositol metabolism. Because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The possibility exists, therefore, that the low concentrations of these compounds in whole brain may be a reflection of a defect in glia or in the proliferation of glial cells during the period of active myelination. In this respect, it is interesting to note that when rats are first introduced to a high galactose diet on weaning at 19 days, the marked fall in Ins concentrations in brain cannot be reproduced (14). Thus, it is possible that once the period of rapid glial proliferation has begun, the brain may be more resistant to the toxic effects of galactose or its metabolites at least with respect to Ins metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility exists, therefore, that the low concentrations of these compounds in whole brain may be a reflection of a defect in glia or in the proliferation of glial cells during the period of active myelination. In this respect, it is interesting to note that when rats are first introduced to a high galactose diet on weaning at 19 days, the marked fall in Ins concentrations in brain cannot be reproduced (14). Thus, it is possible that once the period of rapid glial proliferation has begun, the brain may be more resistant to the toxic effects of galactose or its metabolites at least with respect to Ins metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These include ATP depletion via futile cycles of phosphorylation and dephosphorylation of galactose (Mayes and Miller, 1973), inhibition of key enzymes by galactose-1-phosphate (gal-1P) (Wells et al, 1969; Gitzelmann, 1995; Parthasarathy et al, 1997; Bhat, 2003) and depleted UDP-gal leading to impaired galactosylation of cerebrosides (Lebea and Pretorius, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Gitzelmann (1995) suggested that elevated intracellular gal-1P might inhibit a number of important enzymes, including glucose-6-phosphatase, phosphoglucomutase, liver glycogen phosphorylase, UDP-glucose pyrophosphorylase, glucose 6 phosphate dehydrogenase, and at high concentrations, UDP-gal galactosyltransferase. Although the data remain controversial, other reports suggest that elevated gal-1P may also inhibit myoinositol monophosphatase (Wells et al, 1969;Parthasarathy et al, 1997;Bhat, 2003), the enzyme principally responsible for the production of myo-inositol in many tissues. If true, this inhibition could explain the dramatic loss of both free and lipid-bound myo-inositol observed in brain samples from galactosemia patients (Wells et al, 1965).…”
Section: Connecting the Dotsmentioning
confidence: 95%